2016
DOI: 10.1525/collabra.32
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Categorization on Perceptual Judgment are Robust across Different Assessment Tasks

Abstract: Learned visual categorical perception (CP) effects were assessed using three different measures (similarity rating, same-different judgment, and an XAB task) and two sets of stimuli differing in discriminability and varying on one category-relevant and one category-irrelevant dimension. Participant scores were converted to a common scale to allow assessment method to serve as an independent variable. Two different analyses using the Bayes Factor approach produced patterns of results consistent with learned CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Pothos and Reppa (2014) observed increases in within-category similarity following category learning on a difficult, but not on an easy, problem where the stimuli were arrows which differed in height and width and task difficulty was manipulated by varying the separation of the stimuli along these dimensions. de Leeuw et al (2016) reported a similar effect of task difficultly on acquired equivalence and distinctiveness effects using more complex stimuli. Conversely, Pérez-Gay et al (2017) did not find an effect of stimulus discriminability on categorical perception effects, but their stimuli were textures generated by tessellation of simple checkerboard patterns, and it is arguable that even their most discriminable stimuli were substan-tially more similar than any of the stimuli used by Hall et al (2003) or by Meeter et al (2009).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Pothos and Reppa (2014) observed increases in within-category similarity following category learning on a difficult, but not on an easy, problem where the stimuli were arrows which differed in height and width and task difficulty was manipulated by varying the separation of the stimuli along these dimensions. de Leeuw et al (2016) reported a similar effect of task difficultly on acquired equivalence and distinctiveness effects using more complex stimuli. Conversely, Pérez-Gay et al (2017) did not find an effect of stimulus discriminability on categorical perception effects, but their stimuli were textures generated by tessellation of simple checkerboard patterns, and it is arguable that even their most discriminable stimuli were substan-tially more similar than any of the stimuli used by Hall et al (2003) or by Meeter et al (2009).…”
Section: Discussionmentioning
confidence: 73%
“…These experiments, however, employed simple stimuli and transfer tests where the effects of initial training were observed on the acquisition of a subsequent discrimination. The majority of recent studies of acquired equivalence and distinctiveness in humans have used more complex stimuli and assessed the effects using measures such as similarity ratings, same-different judgements, or an X-AB (or match-to-sample) task (e.g., de Leeuw et al, 2016;Goldstone, 1994;Goldstone & Steyvers, 2001;Livingstone et al, 1998;Notman et al, 2005). In these experiments, participants are typically trained to categorize stimuli that differ along two dimensions where the category boundary lies at the middle of one of the dimensions while the other dimension is irrelevant.…”
Section: Disentangling the Effects Of Attentional Weighting And Assocmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of perceptual learning are restricted to comparing the members of a newly learned category with objects that do not belong to it, and so they do not concern a change in the general ability to compare certain properties (Furmanski and Engel, ). Furthermore, the aforementioned results have been replicated using various experimental designs (see de Leeuw et al ., ; Goldstone and Hendrickson, , for reviews). In consequence, such behavioural data provide a strong reason to believe that even the simplest forms of perceptual learning, which do not involve an obvious phenomenal change, involve a modification in represented lower‐level properties.…”
Section: Dependency Of R‐propertiesmentioning
confidence: 99%
“…In particular, dimensions or feature ranges relevant for the categorical discrimination are encoded more accurately than the ones that are irrelevant to the categorization task (Bates, Lerch, Sims, & Jacobs, 2019; de Beeck, Wagemans, & Vogels, 2003; Folstein, Palmeri, & Gauthier, 2013; Goldstone & Steyvers, 2001; Gureckis & Goldstone, 2008; Hockema, Blair, & Goldstone, 2005; Livingston et al., 1998; Notman, Sowden, & Özgen, 2005). The effects of learned categorical perception have been shown to be robust across different measurement methods, such as similarity ratings, same‐different judgments, and XAB tasks (de Leeuw, Andrews, Livingston, & Chin, 2016).…”
Section: Introductionmentioning
confidence: 99%